WRITING ANXIETY IN ENGLISH ACADEMIC WRITING: A CASE STUDY OF EFL STUDENTS' PERSPECTIVES - Nailis Sa'adah; Fachri Ali (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
Reporting the EFL students' perspectives as their experience in perceiving writing anxiety in English academic writing is the aim of this current study. Designed in a case study, data was collected through a semi-structured interview. Five EFL students at a university in Central Java, Indonesia was recruited to participate in this study. Framed in a thematic analysis, the findings of the study demonstrate that their perspectives were investigated in five aspects: the way they perceive difficult patterns in English academic writing, writing under time and theme constraints, and the way they view and think about the contributions of evaluations and comments from their lecturers and classmates to their writing process and progress. The result of this study showed that the emotive dimension of insecurity was the most apparent in EFL students themselves during writing activities for their English academic writing. This empirical evidence contributes to educational policy balanced to the students' ability.